2022
DOI: 10.3389/fphys.2022.833242
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Metabolomics Platform for the Rapid Data-Driven Development of Novel Additive Solutions for Blood Storage

Abstract: Red blood cell transfusion is a life-saving intervention, and storage is a logistic necessity to make ~110 million units available for transfusion every year worldwide. However, storage in the blood bank is associated with a progressive metabolic decline, which correlates with the accumulation of morphological lesions, increased intra- and extra-vascular hemolysis upon transfusion, and altered oxygen binding/off-loading kinetics. Prior to storage, red blood cells are suspended in nutrient formulations known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 75 publications
0
46
0
Order By: Relevance
“…Recently, through a high-throughput metabolomics platform, the addition of several metabolites was applied to test their influence upon energy and redox metabolism. For example, supplementation of stored RBCs with the antioxidant N-acetylcysteine seemed to beneficially impact the pentose phosphate pathway (PPP), while the addition of glutamine did not alter glutathione (GSH) synthesis, with both results being supported by other studies [ [10] , [11] , [12] ]. Incubation of stored RBCs in fruit and vegetable extracts showed that the bio-flavonoid naringin protected them from lysis and externalization of removal signals [ 13 ], whereas polyphenol quercetin had a minor impact [ 14 ].…”
Section: Introductionmentioning
confidence: 71%
“…Recently, through a high-throughput metabolomics platform, the addition of several metabolites was applied to test their influence upon energy and redox metabolism. For example, supplementation of stored RBCs with the antioxidant N-acetylcysteine seemed to beneficially impact the pentose phosphate pathway (PPP), while the addition of glutamine did not alter glutathione (GSH) synthesis, with both results being supported by other studies [ [10] , [11] , [12] ]. Incubation of stored RBCs in fruit and vegetable extracts showed that the bio-flavonoid naringin protected them from lysis and externalization of removal signals [ 13 ], whereas polyphenol quercetin had a minor impact [ 14 ].…”
Section: Introductionmentioning
confidence: 71%
“…The final candidate(s) can then proceed to a full-unit storage study in the final storage configuration, followed by a clinical study to determine post-transfusion recovery of stored autologous RBCs. Recently, an accompanying paper from Nemkov et al has shown that the overall metabolic profile generated by this platform is comparable to that of RBCs stored in a standard storage bag, and successfully demonstrated the platform’s feasibility by applying it to examine the effect of spiking five different compounds into the AS-3 additive ( Nemkov et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted under both the conventional normoxic (N) condition and hypoxic/hypocapnic (H) storage condition. The study was designed to investigate RBC samples stored under the H condition as well as the standard N storage condition because; i) H storage has been shown to significantly enhance the quality of stored RBCs (Han et al, 2010;Dumont et al, 2016;Nemkov et al, 2022); and ii) the currently approved ASs are not optimized for H storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One main roadblock to the feasibility of remote testing of at home collected blood samples for these emerging medical applications is not only tied to collection and shipment protocols, but also to the intrinsically elevated costs of metabolomics studies. To tackle this issue, we recently developed an ultra‐high‐throughput metabolomics method that enables the analysis of ∼1000 samples/day, making it economically and logistically feasible to scale metabolomics testing for large volumes of samples 74 . Coupling of dried blood field sampling and ultra‐high‐throughput omics approaches can pave the way for the dissemination of metabolomics from a laboratory science to a more widely applicable discipline; a revolution foretold by early application of metabolomics approaches in the fields of clinical biochemistry 75 and medical diagnostics and prognostics, especially when coupled to machine learning approaches 76 .…”
Section: Discussionmentioning
confidence: 99%